Downregulation of RelA (p65) by Rapamycin Inhibits Murine Adipocyte Differentiation and Reduces Fat Mass of C57BL/6J Mice despite High Fat Diet. (23rd January 2014) - Ray, Peter D.; Maclellan, Reid A.; He, Jin; Liu, Zhigang; Wu, Jianguo
Abstract : Rapamycin (RAPA) is a clinical immunosuppressive agent first reported in the literature in 1975 after its discovery in a soil sample from the island of Rapa Nui. Aside from the well-documented effects of RAPA on cell division and immunologic response, the literature reveals it to have negative effects on adipocyte and osteocyte differentiation as well. Understanding of the molecular effects of RAPA on cell differentiation is fragmentary in regard to these cell lineages. In this paper, we examined a potential mechanism for RAPA's effects on adipocyte differentiation in vitro and in vivo . The data point to a unique role of Rel A (p65)—a component of the NF-κ B system—in mediating this event. In murine adipose derived stem cell cultures (muADSCs) from C57BL/6J mice, RAPA was found to selectively downregulate RelA/p65, mammalian target of rapamycin (mTOR), and do so in a dose-dependent manner. This implies a novel role for RelA in adipocyte biology. Intracellular lipid accumulation—as subjectively observed—was also decreased in muADSCs treated with RAPA. Mice treated with RAPA had reduced overall body weight and reduced size of both intraabdominal and subcutaneous fat pads. When treated with RAPA, mice fed a high fat diet did not develop obesity and were not different from their regular diet controls in terms of body weight. These results suggested that RAPA inhibits adipogenesis and lipogenesis of muADSCs resulting in a prevention of obesity in C57BL/6J mice. This inhibition is strong enough to negate the effects of a high fat diet and seems to act by downregulating the RelA/p65 mTOR signaling pathway—a key component of the NF-κ B family.